Emotions, ethics, and cinematic experience : new phenomenological and cognitivist perspectives - Sinnerbrink, Robert (Berghahn Books, 2021)
Since the early 1990s, phenomenology and cognitivism have become two of the most influential approaches to film theory. Yet far from being at odds with each other, both approaches offer important insights on our subjective experience of cinema. Emotions, Ethics, and Cinematic Experience explores how these two approaches might work together to create a philosophy of film that is both descriptively rich and theoretically productive by addressing the key relationship between cinematic experience, emotions, and ethics.